The effectiveness of students' worksheets with liveworksheets on mts students' mathematics learning outcomes - Hartanto, Suryo; Novianti, Yelsi; Gusmania, Yesi (Universitas Riau Kepulauan, 2023)
It is indicated that students' low mathematics learning outcomes are due to inappropriate learning media. The purpose of this research is: 1) The effectiveness of interactive student worksheets with live worksheets on students' mathematics learning outcomes. 2) The effectiveness of learning companion books on students' mathematics learning outcomes, and, 3) Differences in learning outcomes between students who were given worksheet media. live worksheet with students using learning companion book media. This research is experimental research with Quasi-Experimental Design. The research population was VIII grade students at MTs Negeri 1 Batam. The sampling technique is purposive sampling. Data collection uses a test method in the form of descriptive questions, which have been tested for validity and reliability. Hypothesis testing uses a one sample t-test and an independent sample t-test. Based on the research: (1) Interactive student worksheets with live worksheets are effective on student mathematics learning outcomes, with hypothesis test results, significant at 0.000 < 0.05 (2) Learning companion books are not effective on student mathematics learning outcomes, referring Hypothetical results have a significant value of 0.105 > 0.05 and (3) There are differences in learning outcomes between students using worksheet media and live worksheets and students using learning companion book media, referring to the probability value of Sig. (2-tailed) 0.020 < 0.025. Based on the research, it can be concluded that there is effectiveness in using worksheets with live worksheets on the mathematics learning outcomes of VIII grades students at MTs Negeri 1 Batam.